ECONOMIC STUDY TO MEASURE THE EFFICIENCY AND ITEMS OF MARKETING MARGINS OF TOMATO CROP YEAR 2015 AL-TAJI DISTRICT - Jassam, Q. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The aim of this study is to calculate the marketing efficiency to measures range of efficiency of the marketing processes of crop and their satisfaction of consumer demand, and calculate the marketing margin in marketing process for stage producer – whole sale and whole sale- retailer stage, and to fulfillment the requirements the research it is aims . The data was collected from 32 farms of tomato from AL-Taji District_Baghdad province Agricultural season 2015 non covered agriculture. The marketing efficiency of sample low 32. 5, and the absolute marketing margin in stage of wholesaler-retailer was 230 I.d/kg, and retailers importance it was 39.36%, although that relative importance of the retailer profits from the marketing margin about 67.59%,the study recommended to increasing the efficiency the marketing processes to increase the marketing efficiency ad reducing the waste during the marketing processes, and to cultured the farmers about necessity of the marketing processes in side the farm.